El caso de las contrataciones de menos de 8 Unidades Impositivas Tributarias - Herrera Giurfa†, Oscar Fernando (2021)
The mechanism laid out in the peruvian legal system for state entities and companies’ procurement, is through selection procedures as established in the 1993 Constitution. This is materialized through the State Procurement Law. However, this law contains some cases that don’t allow its application. Within these exceptional cases, we find contracts of up to 8 tax units —UIT—. In this sense, from the revision made to  the Procurement Law, its Regulations, the Supreme Decrees related to public procurement, the Directives, the OSCE opinions and our experience as a professor in Public Procurement, we have been able to realize that the legal framework for procurement up to 8 tax units is not clearly established, except in the aspects related to their registration in the SEACE, as provided in paragraph 2 of article 5 of the Law and subclause a) of article 11.2 of the Directive N° 008-2017-OSCE/CD “Provisions applicable to the registration of information in the Electronic System of State Procurement - SEACE”. However, and as we develop in this article, the question remains: what is the applicable regulation for contracts up to 8 tax units? In this sense and considering that this contractual modality is the most used by public entities, considering its amount, its speed, its flexibility, we intend to address this problem and we will try to propose alternative solutions to it.